Muslim Youth and the Challenges of Asylum and Migration in Western Countries and Ways to Face Them From the Point of View of Islamic Jurisprudence Applied Models - Ananbeh, Sewar Ahmed Hussein (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study seeks to explore the challenges faced by Muslim youth in the context of migration and asylum, and how these challenges can be addressed from the perspective of Islamic jurisprudence. It aims to categorize the types of migration, examine the underlying causes, identify key challenges, and propose religiously grounded responses and solutions. Methods: The study employed both inductive and analytical methods. It involved surveying relevant scholarly material, analyzing Islamic juristic opinions, and reviewing international conventions and treaties related to asylum, refugees, and their rights. Results: The study concluded that migration and asylum are driven by various factors, including political, social, and economic pressures. The challenges encountered by Muslim youth in Western countries vary depending on these motivations. Islamic jurisprudence and scholarly councils have addressed concerns such as the risk of losing Islamic identity or religious commitment when residing in non-Muslim countries or acquiring their citizenship. These were met with legal allowances for residence in such contexts in cases of necessity or urgent need. Another major challenge is the education of Muslim children in Western environments. The response emphasized the need to train qualified educators in Islamic universities, colleges, and schools to instill a strong sense of Islamic identity and moral values in Muslim youth. Conclusion: To effectively address these challenges, the study recommends the development of nurturing educational environments as alternatives to morally compromising settings. It also advocates for increasing the number of lectures and training workshops aimed at promoting educational and religious awareness among Muslim youth.